From Traditional to Intelligent: How AI Transforms English Language Learning and Teaching - Wu, Shufen (Digital Technologies Research and Applications, 2026)
In recent years, artificial intelligence has developed quickly, which is changing the English teaching and training in a radical way; the focus is shifting from the original mode to smart tools and software. In light of this, we adopted mixed research methods to investigate such changes in the present study. The research lasted for 16 weeks, using a quasi-experiment research method. Specifically, we explored what the functions of AI are in English learning and teaching. There were a total of 120 undergraduate students and 12 teacher participants in our research. Multiple data collection tools were used: questionnaire survey, class observation, interview, and analysis of learning behavior data. We found that there were obvious improvements in some respects. For example, intelligent pronunciation correction systems improved scores by 29.4 points; AI writing assistant tools brought about gains of 19.5 points; Conversational robots promoted oral ability growth of 20.9 points, with d = 1.96. The adaptive learning platform achieved personalized recommendation accuracy of 87.3%, while differentiated instruction enabled low-proficiency learners to improve by 43.0%. Teacher roles shifted markedly from knowledge transmission toward facilitation, with direct instruction time declining from 62% to 28%. Despite these promising outcomes, challenges including algorithmic bias, technology overdependence, data privacy risks, and digital equity concerns warrant careful consideration. The study concludes that optimal English education requires organic integration of technological efficiency and humanistic pedagogy.